An application of principal component analysis (PCA) using XRF data to delineate the continetality factor over beach sediments from Vengurla, West Coast, Sindhudurg district, Maharashtra, India - Gawali, Praveen; Sangode, Satish; Herlekar, Milind; Kamble, Prafull (My University, 2021)
We present here a novel approach of PCA to delineate the oceanic versus continental influence during pre-mid and post monsoon seasons (PRM, MON, POM) over beach sedimentation at Vengurla along the west coast of India in Sindhudurg district, Maharashtra.PCA conducted over the XRF elemental results from 2003-2004 indicate a factor loading F1 for 2003 depicting predominant ‘oceanic detrital’ process and F2 as ‘continental weathering process. F1 for 2004 indicated ‘continental weathering’ with subdued ‘oceanic detrital’ process. F1 for the MON 2003 indicate ‘continental detrital’ process, and F2 subdued ‘continental weathering’ process. F1 for 2004 reveals ‘continental detrital’ and F2 ‘continental weathering’ process. The overwhelming impact of monsoon can be inferred from this correlation. F1 for 2003 and 2004 POM as well can be assigned to ‘continental detrital’ process, and F2 to subdued ‘continental weathering’ process. The geochemical changes at Vengurla are season dependent, wherein hinterland is drained by monsoonal precipitation. The factor loading approach on mineral magnetic and geochemical data thus presents a precise semiquantitative method to delineate the continental and oceanic influence on the beach placers.
Keywords: PCA; Beach; Oceanic; Continental